The Role of Civil Society within the Democracy - Goga Gina Livioara (EIRP Proceedings, 2009)
The consolidation and development of the lawful state cannot be accomplished without anactive and functional civil society. A functional civil society is the basis of democracy, because ademocracy in which the individuals cannot express their opinions and organize in different kinds oforganizations cannot be considered a democracy. Within the totalitarian states, the existence of a civilsociety cannot be conceived, as the individual’s freedom is constrained. In the present context, the realityof Europe’s liberal democracies is that they are in a strong governmental deadlock, cause by the existenceof a political system in which there isn’t an active civil society or at least a civil society that does notaccept inequalities and government injustice. A corrupt society has at the other pole a weak civil society.The civil society’s role is to monitor and get involved in the corruption issues, being part of the systems ofnational integrity. The society’s welfare in general is reduced in the long run to the citizen’s role, at anindividual level. The ideal citizen must show an interest and participate in the political life, express hispoint of view and get actively involved in the community’s life, helping his neighbours and collaboratingwith the others.